2003
DOI: 10.1590/s0100-879x2003001100005
|View full text |Cite
|
Sign up to set email alerts
|

Comparative sequence analysis of the P-, M- and L-coding region of the measles virus CAM-70 live attenuated vaccine strain

Abstract: Measles virus is a highly contagious agent which causes a major health problem in developing countries. The viral genomic RNA is singlestranded, nonsegmented and of negative polarity. Many live attenuated vaccines for measles virus have been developed using either the prototype Edmonston strain or other locally isolated measles strains. Despite the diverse geographic origins of the vaccine viruses and the different attenuation methods used, there was remarkable sequence similarity of H, F and N genes among all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Previous genetic analyses of coding regions of CAM-70 have considered this vaccine the most divergent member within its clade [21,31]. Our analysis comparing the full genome of CAM-70 with that of other measles vaccines confirms this observation.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Previous genetic analyses of coding regions of CAM-70 have considered this vaccine the most divergent member within its clade [21,31]. Our analysis comparing the full genome of CAM-70 with that of other measles vaccines confirms this observation.…”
Section: Resultssupporting
confidence: 82%
“…Since, the occurrence of nucleotide heterogeneities in measles virus genomic sequences has never been reported, our discussion is limited by the paucity of data on this matter. Notwithstanding, it is important to emphasize the limitation of genome analysis by direct sequencing which is There are three nucleotide differences in the H gene when comparing with the sequence of Rota and coworkers [21], and two nucleotides differences in the P gene when comparing with the sequence of Santos and co-workers [31] (Table 1). In fact, both studies have used a few passages of the CAM-70 virus in Vero cells to obtain the stock used for RNA extraction and cDNA synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the original isolates would have had to spread many times in some way via SLAM-and CD46-independent mechanisms. Available sequence data indicate that all MV vaccine strains have both or either of the P64S and E89K substitutions (32,38,39) (GenBank accession number EF033071). We speculate that at least one of these substitutions is needed for MV to survive in unnatural host cells.…”
Section: Discussionmentioning
confidence: 99%
“…P64S and E89K substitutions were shown to be responsible for the ability of the Edmonston M protein to enable the virus to grow efficiently in Vero cells at postentry steps (45). Examination of published sequence data revealed that all MV vaccine strains have either or both of the P64S and E89K substitutions in their M proteins (32,38,39) (GenBank accession number EF033071).…”
mentioning
confidence: 99%
“…In order to describe the genetic changes that accompany attenuation, the sequences of the genomes of the measles vaccine strains have been compared [Rota et al, 1994;Bankamp et al, 1999Bankamp et al, , 2005Parks et al, 2001a,b;Bankamp et al, 2002;Santos et al, 2003;Liu et al, 2006]. Though partial sequence comparisons were conducted [Rota et al, 1994;Bankamp et al, 2005], the complete genomic sequences of the Chinese vaccines, S-191 and C-47, have not been analyzed.…”
Section: Introductionmentioning
confidence: 99%